2006
DOI: 10.1002/anie.200600556
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Pure Cyclopropenylcarbinols as a Source of Chiral Alkylidenecyclopropane Derivatives

Abstract: The straightforward approach: The copper‐catalyzed carbomagnesiation reaction of chiral cyclopropenylcarbinol derivatives, obtained through kinetic resolution of secondary allylic alcohols, leads to the preparation of enantiomerically pure alkylidenecyclopropane derivatives. The reaction mechanism is composed of a syn carbometalation followed by a syn elimination reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 51 publications
0
47
0
2
Order By: Relevance
“…As the stereogenic quaternary center is at no risk of racemization in the process,the optical purity is identical throughout the rest of the synthesis (Scheme 1). Subsequent oxidative cleavage of the double bond followed by the in situ reduction with NaBD 4 leads to the volatile neopentanol which must be protected in situ to give the tosylate adduct (R [ 16] Thestructure of 2 H 6 -1 was definitively established by 2 HNMR spectroscopy with and without proton decoupling in an isotropic solvent ( Figure 1B,top and bottom). Thus,the presence of three 2 1 Hd ecoupling is turned off (see also the Supporting Information).…”
Section: Dedicated To Professor Duilio Arigonimentioning
confidence: 99%
“…As the stereogenic quaternary center is at no risk of racemization in the process,the optical purity is identical throughout the rest of the synthesis (Scheme 1). Subsequent oxidative cleavage of the double bond followed by the in situ reduction with NaBD 4 leads to the volatile neopentanol which must be protected in situ to give the tosylate adduct (R [ 16] Thestructure of 2 H 6 -1 was definitively established by 2 HNMR spectroscopy with and without proton decoupling in an isotropic solvent ( Figure 1B,top and bottom). Thus,the presence of three 2 1 Hd ecoupling is turned off (see also the Supporting Information).…”
Section: Dedicated To Professor Duilio Arigonimentioning
confidence: 99%
“…82,83 Fox showed that cyclopropenes substituted with suitable leaving groups such as methyl, MEM- and SEM ethers gave a mixture of addition ( 35 ) and addition–elimination ( 36 ) products (Scheme 31). 82 Further investigations showed that the presence of copper salts was not necessary to induce the elimination reaction.…”
Section: Carbocupration Reactions Of Cyclopropenesmentioning
confidence: 99%
“…Such a process is thermodynamically favored due to the relief of strain energy associated with movement of the double bond to the exocyclic position. This approach has been developed for the synthesis of carbon/hydrogensubstituted methylenecyclopropanes [42][43][44][45][46][47], but is also one of the limited ways to prepare heteroatom-substituted systems. One notable example is the strain-driven [3,3]-sigmatropic rearrangement of cyclopropenylmethyl esters to acetoxy-substituted methylenecyclopropanes by Marek and co-workers (eq 1, Scheme 1) [43].…”
mentioning
confidence: 99%